Consumption and Utilization of Leaves of Populus deltoides by the Larva of Spilarctia obliqua (Lepidoptera: Arctiidae) - Faisal, Mohammad; Ahmad, Mukhtar; Singh, K. P. (Indian Forester, 2018)
Spilarctia obliqua is considered as a serious pest of agroforestry importance, which is capable to cause considerable damage to many forestry and agricultural crops in the absence of their primary pest. During present study potentiality of the larvae of S. obliqua in consuming the foliage of Populus deltoides and its utilization was studied. The parameters recorded during study including duration of larval period, consumption of leaf, weight of feacal matter excreted by the larvae, average body weight, increase in body weight, consumption index (C.I.), approximate digestibility (AD), efficiency of conversion of ingested food (E.C.I.) and efficiency of conversion of digested food (E.C.D.).